Solid electrolyte coating, composite diaphragm and application

By using acidic amino acids in solid electrolyte coatings with fluorine- or oxygen-containing substituent binders, the bonding ability and peel strength are enhanced, and the problem of insufficient peeling strength of solid electrolyte-coated separators in the battery cell is solved, and the problem of insufficient peeling strength of solid electrolyte-coated separators in the battery cell is improved. Capacity retention and cycle stability of lithium/sodium ion batteries.

CN119133583APending Publication Date: 2024-12-13LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458107.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing solid electrolyte-coated separator has insufficient peeling strength in the battery cell and is prone to fall off during the electrolyte soaking, affecting the performance of the battery cell. Introducing too much binder will reduce the breathability and affect the diffusion of lithium ions.

Method used

Acid amino acids are used as binder enhancers, and binders containing fluorine or oxygen-containing substituents are combined to enhance the bonding ability and reduce the surface energy of solid electrolyte particles, thereby improving coating. The peel strength and wettability of the layer reduce the amount of binder.

Benefits of technology

Improve the peel strength and wettability of the solid electrolyte coating, reduce the surface energy of the solid electrolyte, enhance the coating effect of lithium and sodium solid electrolyte particles, avoid additives blocking the separator holes, and improve the lithium/sodium ion battery. Capacity retention and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a solid electrolyte coating, a composite diaphragm and application, the solid electrolyte coating comprises a solid electrolyte, a binder and a wetting agent, and also comprises acidic amino acid as a binder reinforcing agent; the acidic amino acid comprises one or more of aspartic acid, glutamic acid and near-end cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte; the binder has a fluorine-containing substituent group and / or an oxygen-containing substituent group. The amino acid is used for enhancing the bonding capacity of the adhesive and enhancing the peel strength of the coated diaphragm, so that the consumption of auxiliaries such as the adhesive is reduced, and diaphragm holes are prevented from being blocked by excessive auxiliaries. Lewis alkaline sites exist on the surface of the adopted lithium and sodium solid electrolyte, amino acid molecules are combined with the Lewis alkaline sites through carboxyl, solid electrolyte particles are coated, and the coating can reduce the surface energy of the lithium and sodium solid electrolyte particles and enhance the wettability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a solid electrolyte coating, a composite diaphragm and applications. Background Art

[0002] Solid electrolyte coated diaphragms are favored by the lithium and sodium ion battery industries because of their conductivity enhancement and lithium replenishment effects. At present, the preparation of slurry for solid electrolyte coated diaphragms mostly draws on the formula of traditional alumina coated diaphragms. Compared with neutral alumina, solid electrolytes are usually rich in lithium ions, which will produce a large number of Lewis basic sites on the particle surface, affecting the role of additives such as dispersants, binders and wetting agents. Therefore, it is necessary to make major adjustments to the slurry formula, or even develop new additives.

[0003] When applying solid electrolyte coated diaphragms to battery cells, it is important to consider the peel strength of the coated diaphragms to prevent the diaphragms from falling off during immersion in the electrolyte and adversely affecting the performance of the battery cells. However, introducing too much binder will reduce the permeability of the diaphragm and affect the diffusion of lithium ions through the diaphragm. Summary of the invention

[0004] The purpose of the present invention is to provide a solid electrolyte coating, a composite diaphragm and applications. The peel strength between the solid electrolyte coating and the diaphragm in the present invention is high and the surface energy of the solid electrolyte can be reduced.

[0005] The present invention provides a solid electrolyte coating, comprising a solid electrolyte, a binder and a wetting agent, and also comprising an acidic amino acid as a binder reinforcing agent;

[0006] The acidic amino acid includes one or more of aspartic acid, glutamic acid and proximal cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte;

[0007] The binder has a fluorine-containing substituent and / or an oxygen-containing substituent.

[0008] Preferably, the binder includes one or more of carboxymethyl acrylate, carboxymethyl cellulose salt, polyacrylate and polyvinylidene fluoride.

[0009] Preferably, the mass of the binder is 1-1.5% of the mass of the solid electrolyte.

[0010] Preferably, the surface of the solid electrolyte has Lewis basic sites, and the aqueous solution of the solid electrolyte is alkaline.

[0011] Preferably, the solid electrolyte includes a lithium solid electrolyte or a sodium solid electrolyte, the lithium solid electrolyte includes LLZO and / or LLTO, and the sodium solid electrolyte includes one or more of NZSP, β-Al2O3, β′′-Al2O3 and Na3AlF6.

[0012] The present invention provides a method for preparing the solid electrolyte coating as described above, comprising the following steps:

[0013] A) grinding and mixing the solid electrolyte and the acidic amino acid to obtain a grinding slurry;

[0014] B) mixing the grinding slurry, the binder and the wetting agent to obtain a coating slurry;

[0015] C) coating the coating slurry on the surface of a substrate, and obtaining a solid electrolyte coating after drying.

[0016] Preferably, the drying temperature in step C) is 30-50° C., and the drying time in step C) is 1-10 min.

[0017] The present invention provides a composite diaphragm, comprising a diaphragm substrate and a solid electrolyte coating composited on the surface of the diaphragm substrate;

[0018] The solid electrolyte coating is the solid electrolyte coating described above or a solid electrolyte coating prepared by the preparation method described above.

[0019] The present invention provides a lithium / sodium ion secondary battery, comprising the composite diaphragm described above.

[0020] The present invention provides the use of an acidic amino acid as a binder enhancer in improving the bonding ability of a solid electrolyte coating, wherein the acidic amino acid comprises one or more of aspartic acid, glutamic acid and proximal cysteine;

[0021] The binder has a fluorine-containing substituent and / or an oxygen-containing substituent.

[0022] The present invention provides a solid electrolyte coating, comprising a solid electrolyte, a binder and a wetting agent, characterized in that it also comprises an acidic amino acid as a binder enhancer; the acidic amino acid comprises one or more of aspartic acid, glutamic acid and proximal cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte; the binder has a fluorine-containing substituent and / or an oxygen-containing substituent. The present invention uses amino acids to enhance the bonding ability of the binder, and the amino groups in the amino acids can generate hydrogen bonds with the fluorine-containing or oxygen-containing substituents in the binder, thereby generating stronger interactions with the molecular chains of the polymer binder, improving the bonding effect of the binder, and enhancing the peel strength of the coated diaphragm, which is conducive to reducing the amount of auxiliary agents such as the binder, and preventing the auxiliary agents from excessively clogging the diaphragm pores. In order to further achieve this gain effect, the surface of the lithium and sodium solid electrolytes used has Lewis basic sites, and the amino acid molecules are combined with the Lewis basic sites through carboxyl groups to achieve the coating of the solid electrolyte particles. This coating also reduces the surface energy of the lithium and sodium solid electrolyte particles and enhances wettability. DETAILED DESCRIPTION

[0023] The present invention provides a solid electrolyte coating, comprising a solid electrolyte, a binder and a wetting agent, and also comprising an acidic amino acid as a binder reinforcing agent;

[0024] The acidic amino acid includes one or more of aspartic acid, glutamic acid and proximal cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte;

[0025] The binder has a fluorine-containing substituent and / or an oxygen-containing substituent.

[0026] In the present invention, the surface of the solid electrolyte preferably has Lewis basic sites, and the aqueous solution of the solid electrolyte is alkaline, so that the acidic amino acid molecules as the binder enhancer can bind to the Lewis basic sites through the carboxyl group to achieve the coating of the solid electrolyte particles, so as to reduce the surface energy of the solid electrolyte particles. The solid electrolyte is preferably a lithium solid electrolyte or a sodium solid electrolyte, the lithium solid electrolyte includes LLZO and / or LLTO, and the sodium solid electrolyte includes one or more of NZSP, β-Al2O3, β′′-Al2O3 and Na3AlF6; the particle size of the solid electrolyte is preferably 300~600nm.

[0027] In the present invention, the binder preferably has a fluorine-containing substituent and / or an oxygen-containing substituent, and is preferably one or more of carboxymethyl acrylate, carboxymethyl cellulose salt, polyacrylate and polyvinylidene fluoride (PVDF); the mass of the binder is 1-1.5% of the mass of the solid electrolyte, and more preferably 1.2-1.4%, such as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0028] In the present invention, the acidic amino acid is added to the solid electrolyte coating as a binder enhancer to enhance the bonding ability of the binder and the glass strength of the coating, thereby reducing the amount of the binder while improving the bonding performance of the coating and preventing the additive from excessively clogging the diaphragm pores. The acidic amino acid includes one or more of aspartic acid, glutamic acid and proximal cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte, and more preferably 0.5-0.6%.

[0029] In the present invention, the wetting agent preferably includes one or more of sodium dodecyl sulfate, a condensate of a fatty alcohol and ethylene oxide, and the mass of the wetting agent is 0.15-0.2% of the mass of the solid electrolyte, and more preferably 0.16-0.18%, such as 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0030] The present invention also provides a method for preparing the solid electrolyte coating as described above, comprising the following steps:

[0031] A) grinding and mixing the solid electrolyte and the acidic amino acid to obtain a grinding slurry;

[0032] B) mixing the grinding slurry, the binder and the wetting agent to obtain a coating slurry;

[0033] C) coating the coating slurry on the surface of a substrate, and obtaining a solid electrolyte coating after drying.

[0034] In the present invention, the types and amounts of the solid electrolyte and the acidic amino acid are consistent with the types and amounts of the solid electrolyte and the acidic amino acid described above, and the present invention will not be repeated here.

[0035] In the present invention, the acidic amino acid is preferably added in batches during the grinding process of the solid electrolyte. For example, during the grinding process, a portion of the acidic amino acid is added every time the particle size decreases by 100 to 300 nm until the particle size of the solid electrolyte reaches the required value and all the acidic amino acids are added. The grinding is preferably sand grinding, and the solid content of the grinding slurry is preferably 30 to 40 wt %.

[0036] In the present invention, the type and amount of the binder and wetting agent are consistent with the type and amount of the binder and wetting agent described above, and the present invention will not be repeated here.

[0037] In the present invention, there is no particular limitation on the coating method, and the coating methods commonly used in the art, such as blade coating, spin coating, roller coating, etc., can be used.

[0038] In the present invention, the drying temperature is preferably 30-50° C., more preferably 35-40° C., and the drying time is preferably 1-10 min, more preferably 3-8 min, and most preferably 5-6 min.

[0039] The present invention also provides a composite diaphragm, comprising a diaphragm substrate and a solid electrolyte coating composited on the surface of the diaphragm substrate, wherein the solid electrolyte coating is the solid electrolyte coating described above.

[0040] In the present invention, the diaphragm substrate is preferably a PE diaphragm, a PP diaphragm, a PE / PP laminated diaphragm, or a PI diaphragm.

[0041] In the present invention, the thickness of the solid electrolyte coating is preferably 1 to 5 μm, more preferably 2 to 4 μm.

[0042] The present invention also provides a secondary battery, comprising the composite separator described above.

[0043] The secondary battery also includes conventional positive electrode, negative electrode and electrolyte. The present invention does not impose any special restrictions on the types of the positive electrode, negative electrode and electrolyte. The positive electrode, negative electrode and electrolyte commonly used in the art can be used.

[0044] The lithium / sodium solid electrolyte coating can improve the wettability to the electrolyte. At the same time, the lithium / sodium solid electrolyte can provide partial ion conductivity and have a lithium / sodium supplement effect, thereby improving the capacity of the battery and the capacity retention rate after long cycles.

[0045] The present invention provides an application of an acidic amino acid as a binder enhancer in improving the bonding ability of a solid electrolyte coating, i.e., a method for improving the bonding ability of a coating by adding an acidic amino acid into a solid electrolyte, wherein the acidic amino acid comprises one or more of aspartic acid, glutamic acid and proximal cysteine; and the binder has a fluorine-containing substituent and / or an oxygen-containing substituent.

[0046] In the present invention, the composition, content and preparation method of the solid electrolyte coating are consistent with the composition, content and preparation method of the solid electrolyte coating described above, and the present invention will not repeat them here.

[0047] The present invention provides a solid electrolyte coating, including a solid electrolyte, a binder and a wetting agent, characterized in that it also includes an acidic amino acid as a binder enhancer; the acidic amino acid includes one or more of aspartic acid, glutamic acid and proximal cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte; the binder has a fluorine-containing substituent and / or an oxygen-containing substituent. The present invention uses amino acids to enhance the bonding ability of the binder. The amino group in the amino acid can generate hydrogen bonds with the fluorine-containing or oxygen-containing substituents in the binder, thereby generating stronger interactions with the molecular chains of the polymer binder, improving the bonding effect of the binder, and enhancing the peel strength of the coated diaphragm, which is conducive to reducing the amount of auxiliary agents such as the binder and preventing the auxiliary agents from excessively clogging the diaphragm pores. In order to achieve this gain effect, it is necessary to have Lewis basic sites on the surface of lithium and sodium solid electrolytes. The amino acid molecules bind to the Lewis basic sites through carboxyl groups to achieve coating of the solid electrolyte particles. This coating also reduces the surface energy of lithium and sodium solid electrolyte particles.

[0048] In order to further illustrate the present invention, a solid electrolyte coating, a composite diaphragm and applications provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0049] Example 1

[0050] 1. LLZO solid electrolyte coated diaphragm:

[0051] Large-sized LLZO particles were crushed by a sand mill at a speed of 1800 rpm. During the sand milling process, part of aspartic acid was added every time the particle size decreased by 200 nm until the LLZO particle size decreased to 300-500 nm. The total amount of aspartic acid added was 0.5 wt% of the mass of LLZO, and the solid content of the slurry was 30 wt%. A binder (polyacrylate polymer, purchased from Hunan Gaorui Power Material Co., Ltd., model GR506) and a wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were added to the sand-milled slurry in sequence, wherein the binder content was 1 wt% of the mass of LLZO in the slurry, and the wetting agent was 0.15 wt% of the mass of LLZO in the slurry. After mixing evenly, the slurry was coated on the PE base film by roller coating, and the coating thickness was controlled to be 2 μm, and double-sided coating was performed.

[0052] 2. Assembly of button cells with graphite as negative electrode:

[0053] The NCM811 positive electrode active material, conductive carbon black, and binder were added to NMP at a weight ratio of 96: 1.5: 2.5 and mixed evenly. The positive electrode slurry was evenly coated on both surfaces of the aluminum foil, and then dried, rolled, and cut to obtain the positive electrode sheet. The negative electrode active materials graphite, SP, binder styrene butadiene rubber (SBR), and thickener (CMC) were added to the solvent deionized water at a weight ratio of 96.2: 0.8: 0.8: 1.2, and the mixed negative electrode slurry was evenly coated on both surfaces of the copper foil, and then dried, rolled, and cut to obtain the negative electrode sheet.

[0054] The dried negative electrode sheet, separator, and positive electrode sheet are stacked in order to obtain a battery cell assembly, and the electrolyte is injected after packaging. After packaging, standing, and forming, a battery cell is obtained. The rated capacity of the soft-pack battery cell is 2Ah, and the injection amount is 9g. To ensure the credibility of the data, three batteries are assembled in parallel, numbered as Examples 1.1-1.3.

[0055] Comparative Example 1

[0056] Comparative Example 1 is the same as the cell assembly method in Example 1, and the diaphragm used is a LLZO coated diaphragm. The diaphragm coating scheme is as follows: LLZO particles are crushed by a sand mill at a speed of 1800 rpm until the LLZO particle size is reduced to 300-500nm, and the slurry solid content is 30wt%. A binder and a wetting agent (the binder and wetting agent models are the same as in Example 1) are added to the sand-milled slurry in sequence, wherein the binder content is 1.5wt% of the mass of LLZO in the slurry, and the wetting agent is 0.15wt% of the mass of LLZO in the slurry. After mixing evenly, the slurry is coated on the PE base film by roller coating, and the coating thickness is controlled to be 2μm, and double-sided coating is performed.

[0057] To ensure the credibility of the data, three battery cells were assembled in parallel and numbered as comparative examples 1.1-1.3.

[0058] Comparative Example 2

[0059] Comparative Example 2 is the same as the cell assembly method of Example 1, but the diaphragm used is a PE diaphragm coated with α-Al2O3 (purchased from Anhui Yishitong Material Technology Co., Ltd.), and the diaphragm coating scheme is as follows: α-Al2O3 particles are crushed by a sand mill at a speed of 1800 rpm. During the sand milling process, part of aspartic acid is added for every 200nm reduction in particle size until the α-Al2O3 particle size is reduced to 300-500nm, and the total amount of aspartic acid added is 0.5wt% of the mass of α-Al2O3, and the solid content of the slurry is 30wt%. A binder and a wetting agent (the binder and wetting agent models are the same as in Example 1) are added to the sand milled slurry in sequence, wherein the binder content is 1wt% of the mass of α-Al2O3 in the slurry, and the wetting agent is 0.15wt% of the mass of α-Al2O3 in the slurry. After mixing evenly, the slurry is coated on the PE base film by roller coating, and the coating thickness is controlled to be 2μm, and double-sided coating.

[0060] To ensure the credibility of the data, three battery cells were assembled in parallel and numbered as comparative examples 2.1-2.3.

[0061] Example 2

[0062] 1. NZSP solid electrolyte coated diaphragm:

[0063] The cell assembly method of Example 2 is the same as that of Example 1, but the diaphragm used is a PE diaphragm coated with NZSP. The diaphragm coating scheme is as follows: large-sized NZSP particles are crushed by a sand mill at a speed of 1800 rpm. During the sand milling process, part of aspartic acid is added for every 200 nm reduction in particle size until the NZSP particle size is reduced to 300-500 nm. The total mass of aspartic acid added is 0.5 wt% of the mass of NZSP, and the solid content of the slurry is 30 wt%. A binder and a wetting agent (the binder and wetting agent models are the same as those of Example 1) are added to the sand milled slurry in sequence, wherein the binder content is 1 wt% of the mass of NZSP in the slurry, and the wetting agent is 0.15 wt% of the mass of NZSP in the slurry. After mixing evenly, the slurry is coated on the PE base film by roller coating, and the coating thickness is controlled to be 2 μm, and double-sided coating is performed.

[0064] 2. Assembly of button cells with metallic sodium as negative electrode:

[0065] The sodium vanadium phosphate positive electrode active material, conductive carbon black, and binder are added to NMP at a weight ratio of 94: 2.5: 3.5 and mixed evenly. The positive electrode slurry is evenly coated on both surfaces of the aluminum foil, and further dried, rolled, and cut to obtain the positive electrode sheet. The negative electrode active material hard carbon, SP, binder styrene butadiene rubber (SBR), and thickener (CMC) are added to the solvent deionized water at a weight ratio of 96.2: 0.8: 0.8: 1.2, and the mixed negative electrode slurry is evenly coated on both surfaces of the copper foil, and the negative electrode sheet is obtained after drying, rolling, and cutting.

[0066] The dried negative electrode sheets, separators, and positive electrode sheets are stacked in order to obtain a battery cell assembly, and the electrolyte is injected after packaging. After packaging, standing, and forming, a battery cell is obtained. The rated capacity of the soft-pack battery cell is 1Ah, and the injection volume is 4.5g.

[0067] To ensure data credibility, three cells were assembled in parallel and numbered as Examples 2.1-2.3.

[0068] Example 3

[0069] The cell assembly method of Example 3 is the same as that of Example 1. The diaphragm used is a PE diaphragm coated with LLZO. The diaphragm coating scheme is as follows: large-sized LLZO particles are crushed by a sand mill at a speed of 1800 rpm. During the sand milling process, part of aspartic acid is added for every 200 nm reduction in particle size until the LLZO particle size is reduced to 300-500 nm. The total mass of aspartic acid added is 0.5 wt% of the mass of LLZO, and the solid content of the slurry is 30 wt%. A binder (PVDF binder, purchased from Kruder Chemical Technology (Shanghai) Co., Ltd., model PVDF5130) and a wetting agent (wetting agent model is the same as in Example 1) are added to the sand milled slurry in sequence, wherein the binder content is 1 wt% of the mass of LLZO in the slurry, and the wetting agent is 0.15 wt% of the mass of LLZO in the slurry. After mixing evenly, the slurry is coated on the PE base film by roller coating, and the coating thickness is controlled to be 2 μm, and double-sided coating is performed.

[0070] To ensure data credibility, three cells were assembled in parallel and numbered as Examples 3.1-3.3.

[0071] Comparative Example 3

[0072] A battery cell was prepared and assembled according to the steps in Example 1, except that an equal amount of lysine was used in Comparative Example 3 to replace the aspartic acid in Example 1.

[0073] To ensure the credibility of the data, three battery cells were assembled in parallel and numbered as comparative examples 3.1-3.3.

[0074] Determination of battery cell capacity retention rate:

[0075] At 25°C, the lithium-ion battery cells in the examples and comparative examples were charged to 4.15V at a constant current of 0.5C, then charged to a current of 0.05C at a constant voltage of 4.15V, left for 5 minutes, and discharged to 2.8V at 0.5C. The measured discharge capacity was recorded as the initial capacity C0. Repeat the above steps for the same battery, and simultaneously record the discharge capacity C100 of the battery after 100 cycles. The battery capacity retention rate after the cycle = 100% × C100 / C0. Diaphragm peel strength test method:

[0076] The instrument used is a universal tensile testing machine. The diaphragm is cut into strips of 30 mm × 200 mm, and the diaphragm is bonded to a stainless steel plate with an area much larger than the diaphragm sample by double-sided tape. A 2 kg roller is used to roll back and forth in the horizontal direction for 3 times. The end of the steel plate with the sample to be tested that is not attached with double-sided tape is fixed to the upper chuck. The test speed is 200 mm / min. The peel force test is completed and the peel strength is calculated.

[0077] Table 1 Performance data of the separators and cells of the examples and comparative examples

[0078]

[0079] Example 1 and Example 2 show that this solution is equally applicable to lithium / sodium ion batteries.

[0080] In Example 1, compared with Comparative Example 1, 0.5 wt % of the binder is replaced with aspartic acid. The use of aspartic acid can significantly improve the peel strength of the diaphragm, prevent the diaphragm from falling off during battery assembly, or the coating from falling off during electrolyte immersion, thereby affecting the electrode reaction. Therefore, the capacity retention rate of the battery cell in Example 1 is higher after 100 cycles.

[0081] Compared with Comparative Example 2, in Example 1, LLZO in the diaphragm coating can release lithium ions through reduction reaction and concentration difference at the solid-liquid interface to replenish lithium. Therefore, the battery cell in Example 1 shows higher first-cycle capacity and 100-cycle capacity retention rate.

[0082] In Comparative Example 3, the basic amino acid lysine was used, which could not bind to the Lewis basic sites on the surface of the solid electrolyte, and thus failed to enhance the binder effect.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A solid electrolyte coating, comprising a solid electrolyte, a binder and a wetting agent, characterized in that: Also included is the use of acidic amino acids as binder enhancers; The acidic amino acid includes one or more of aspartic acid, glutamic acid and proximal cysteine; the mass of the acidic amino acid is 0.4-0.6% of the mass of the solid electrolyte; The binder has a fluorine-containing substituent and / or an oxygen-containing substituent.

2. The solid electrolyte coating according to claim 1, characterized in that: The binder includes one or more of carboxymethyl acrylate, carboxymethyl cellulose salt, polyacrylate and polyvinylidene fluoride.

3. The solid electrolyte coating according to claim 2, characterized in that: The mass of the binder is 1-1.5% of the mass of the solid electrolyte.

4. The solid electrolyte coating according to claim 1, characterized in that: The surface of the solid electrolyte has Lewis basic sites, and the aqueous solution of the solid electrolyte is alkaline.

5. The solid electrolyte coating according to claim 4, characterized in that: The solid electrolyte includes a lithium solid electrolyte or a sodium solid electrolyte. The lithium solid electrolyte includes LLZO and / or LLTO. The sodium solid electrolyte includes one or more of NZSP, β-Al2O3, β′′-Al2O3 and Na3AlF6.

6. The method for preparing the solid electrolyte coating according to claim 1, comprising the following steps: A) grinding and mixing the solid electrolyte and the acidic amino acid to obtain a grinding slurry; B) mixing the grinding slurry, the binder and the wetting agent to obtain a coating slurry; C) coating the coating slurry on the surface of a substrate, and obtaining a solid electrolyte coating after drying.

7. The preparation method according to claim 6, characterized in that: The drying temperature in step C) is 30-50° C., and the drying time in step C) is 1-10 min.

8. A composite diaphragm, comprising a diaphragm substrate and a solid electrolyte coating composited on the surface of the diaphragm substrate; The solid electrolyte coating is the solid electrolyte coating according to any one of claims 1 to 5 or the solid electrolyte coating prepared by the preparation method according to any one of claims 6 to 7.

9. A lithium / sodium ion secondary battery, characterized in that: Comprising the composite diaphragm as described in claim 8.

10. Use of an acidic amino acid as a binder enhancer in improving the bonding ability of a solid electrolyte coating, wherein the acidic amino acid comprises one or more of aspartic acid, glutamic acid and proximal cysteine; The binder has a fluorine-containing substituent and / or an oxygen-containing substituent.